Análisis del impacto de la educación sexual en las y los estudiantes de los segundos de bachillerato de la sección matutina en el colegio “Pio Jaramillo Alvarado” y la intervención del trabajador social en el área educativa durante el periodo 2014- 2015 - Nazareno Herrera, Blanca Victoria (2016)
Adolescence is a stage of experimentation, discovery, of search of its own identity within a group and the family relationship. The ease of access to the erroneous information on sexuality, on contraceptive methods and ways to avoid premature pregnancies affect the decisions of adolescents to begin sexual relations coital in addition to the pressure of the group or the curiosity. Considering that the panorama at the moment on sexual relations among adolescents at an early age is increasing and that the enjoyment of their sexuality in every sense of the word is in danger, which causes wear of values and loss of identity, not only in our country but at the global level, Latin American and national according to what official is seen and heard in the different means of communication and also with the broadcast that today has the progress of internet technology. In this scenario it was deemed appropriate to investigate "ANALYSIS OF THE IMPACT OF SEX EDUCATION IN AND STUDENTS OF THE SECONDS OF BACHELOR OF THE MORNING SECTION IN THE COLLEGE "PIO JARAMILLO ALVARADO" AND THE INTERVENTION OF SOCIAL WORKERS IN THE AREA OF EDUCATION DURING THE PERIOD 2014- 2015", where you can identify what happens with the teenagers, what type of information are getting about sexuality and what sources, what their motivation to start and maintain sexual relations coital at an early age, the causes and consequences of the same; this information served us to discuss possible solutions to provide effective information to adolescents in this area and to encourage them to be actors of a change of Mentality not only in them but in the same professionals and adults around them. This is intended to undertake actions that contribute to the improvement of the quality of life of the students; as well as promote a proposal for intervention to prevent adolescents continue to have erroneous information their sexuality and therefore take hasty decisions on the same. The purpose of this research was to explore the knowledge about sexuality provided by teachers and family to adolescents; in addition, to detect the influence of these on the sexual behavior and life of the same. The interpersonal relations and experiential of youth sexuality are marked by the life in the home for the friendships and the student life but the strongest without doubt is the home. It is also proposed to identify the problems that affect them and that are perceived by the and the young people in the areas of sexual education and sexual and reproductive health. In-depth study of the youth sexuality, it means acknowledging that the subject, man and woman, gives a specific meaning to their sexuality according to its own culture and construction of gender, therefore, special attention has been given to the sexual approaches from the scientific point of view, religious and cultural life of the sexuality, for which it uses the scientific method, with the aim of collecting information that will allow this research is veridical and reliable. In this way after having carefully studied this serious problem as is the irresponsible sexual education that is limiting our teenagers to the genital sex education through a number of campaigns on contraceptives and sex that are exposing the family, values and leading us toward a society devoid of affectivity and full of perversion, reality in which are exposed these students because it is a chain of ignorance departing from their same authorities, and parents who moves by the persistent influence of who have already experienced at all, on those that have not done so, it became necessary to the construction of a proposal of intervention with relevant strategies and a knowledge Wide on the subject that will propose alternative solutions to overcome this problem that can lead to improving the quality of life of the students. The analysis provided in this investigative work invites us to reflect on what is happening in the present with adolescents remain so as future Social Worker affects me ensure the integral well-being of the human being, Inter